Reorientation for National Transformation: the Role of Literature - Nnabuihe, Chigozie Bright (Afrika Focus, 2019)
At the formative period of any human society, certain relevant orientations are conceived, designed and actualized to create awareness of what should be acceptable and/or unacceptable in human relationships. There are core values, norms and morals aimed at guiding the behaviour of the native population and making them aware of their place, time and identity within their society. The sole aim of such orientations is to ensure cohesion and a peaceful harmonious existence. Oral literature as it is referred to in this paper points to those literary artistic creations composed in oral form for the purposes of entertainment, edification and education. In the paper, we limit our discussions to the oral version of literature, drawing most of the excerpts from the works of oral Igbo literary artists. A few instances are also drawn from the written version as the need arises. KEYWORDS: RE-ORIENTATION, NATIONAL TRANSFORMATION, ROLE, ORAL IGBO LITERATURE